Growing‐season temperature and precipitation are independent drivers of global variation in xylem hydraulic conductivity. (10th December 2019) - He, Pengcheng; Gleason, Sean M.; Wright, Ian J.; Weng, Ensheng; Liu, Hui; Zhu, Shidan; Lu, Mingzhen; Luo, Qi; Li, Ronghua; Wu, Guilin; Yan, Enrong; Song, Yanjun; et al.
Abstract: Stem xylem‐specific hydraulic conductivity ( K S ) represents the potential for plant water transport normalized by xylem cross section, length, and driving force. Variation in K S has implications for plant transpiration and photosynthesis, growth and survival, and also the geographic distribution of species. Clarifying the global‐scale patterns of K S and its major drivers is needed to achieve a better understanding of how plants adapt to different environmental conditions, particularly under climate change scenarios. Here, we compiled a xylem hydraulics dataset with 1, 186 species‐at‐site combinations (975 woody species representing 146 families, from 199 sites worldwide), and investigated how K S varied with climatic variables, plant functional types, and biomes. Growing‐season temperature and growing‐season precipitation drove global variation in K S independently. Both the mean and the variation in K S were highest in the warm and wet tropical regions, and lower in cold and dry regions, such as tundra and desert biomes. Our results suggest that future warming and redistribution of seasonal precipitation may have a significant impact on species functional diversity, and is likely to be particularly important in regions becoming warmer or drier, such as high latitudes. This highlights an important role for K S in predicting shifts in community composition in the face of climate change. Abstract : Growing‐season temperature and growing‐season precipitation drove global variation in stem xylem‐specific hydraulic conductivity ( K S ) independently. Both the mean and the variation in K S were highest in the warm and wet tropical regions, and lower in cold and dry regions, such as tundra and desert biomes. Our results suggest that future warming and redistribution of seasonal precipitation may have a significant impact on species functional diversity, and is likely to be particularly important in regions becoming warmer or drier, such as high latitudes.